NEBIVOLOL: HAEMODYNAMIC EFFECTS AND CLINICAL SIGNIFICANCE OF COMBINED BETA-BLOCKADE AND NITRIC OXIDE RELEASE - Otto Kamp; Marco Metra; Silvia Bugatti; Luca Bettari; Alessandra Dei Cas; Natalia Petrini; Livio Dei Cas (Российский кардиологический журнал, 2010)
.